Delineation of the Rompin River Basin and network using various GIS applications - Chong, Tat Ming (2019)
Rompin River Basin especially at the downstream region is highly prone to monsoon flood or flash flood. Flooding areas are closely depending on the topographical elevation in the basin where lower ground is more likely to be affected. Thus, it is essential to extract the physical characteristics of the basin to be integrated in flood analysis. The objectives of this study are to delineate river networks and catchment for the Rompin River Basin using different GIS applications, and evaluate the performance of the GIS applications. Digital Elevation Model (DEM) of 30 m resolution was applied in both GIS application tools (ArcGIS and QGIS) for the delineation of the river network and basin. The delineation processes include river network conditioning, fill sink process, flow accumulation process, drainage network extraction process and watershed basin extraction process. The simulated river network from ArcGIS and QGIS were evaluated and compared with the digitized river network from Google map for their performances. The physical characteristics from two GIS application tools were compared and tabulated in this research. For the area of the watershed basin, ArcGIS has an area of 4185 km2 and QGIS has an area of 4234 km2. The perimeter of the watershed basin for ArcGIS is 651 km, while QGIS has a perimeter of 718 km. The minimum elevation for ArcGIS and QGIS are -16 and 2 respectively, while for the maximum elevation for ArcGIS and QGIS are 988 and 804. For the river attributes, ArcGIS has around 771 attributes, while QGIS has around 93 attributes. The average error percentage for three different elevation has been evaluated which are high elevation, intermediate elevation and low elevation. For ArcGIS, the value obtained for high ,intermediate and low elevation are 188m, 240m and 470m, while for the QGIS, the value obtained for high ,intermediate and low elevation are 217m, 446m and 485m. Comparing the result obtained from ArcGIS and QGIS to the digitized river network, it is found that ArcGIS application can delineate the river network more accurately at the intermediate and high elevation, while QGIS can only perform better at high elevation. Although QGIS can be download for free on website, however it can only perform well on high elevation. Since the flood problem is normally occur in lower elevation, QGIS may not be sufficient to be used to delineate the river network at lower level in this study.